World Environmental and Water Resource Congress 2020 Water, Wastewater, and Stormwater and Water Desalination and Reuse - Ahmad, Sajjad (Civil engineer); Murray, Regan (Online access: American Society of Civil Engineers (ASCE) American Society of Civil Engineers (ASCE) Conference Proceedings., 2020)
Selected papers from the World Environmental and Water Resources Congress 2020, held in Henderson, Nevada, May 17-21, 2020. Sponsored by the Environmental and Water Resources Institute of ASCE.This collection contains29 peer-reviewed papers on wastewater, stormwater, and water desalination and reuse.Topics include: modeling and analysis of desalination processes; stormwater management and flood control; low impact development and runoff; and wastewater treatment.This proceedings will be of interest to practitioners and researchers in all areas of water and environmental engineering.